2019
DOI: 10.1089/fpd.2018.2586
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak ofListeria monocytogenesin South Africa, 2017–2018: Laboratory Activities and Experiences Associated with Whole-Genome Sequencing Analysis of Isolates

Abstract: In South Africa, a progressive increase in listeriosis cases was noted from mid-June 2017, heralding what was to become the world's largest listeriosis outbreak. A total of 1060 cases were reported for the period January 1, 2017 to July 17, 2018. We describe laboratory activities, experiences, and results of whole-genome sequencing (WGS) analysis of Listeria monocytogene s isolates associated with this outbreak. Bacteria were identified using the VITEK-2 COMPACT 15 microbial identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(135 citation statements)
references
References 31 publications
4
128
0
3
Order By: Relevance
“…The predominant clonal complexes in China are CC9 and CC8 in food and ST87 in clinics [53,54]. In the last decade, CC6 noticeably increased in significance as a causative agent of human listeriosis in Africa, Europe, and North America [31,33,[55][56][57]. In Russia, current human listeriosis is associated with the CC1, CC2, and CC20 strains [38].…”
Section: Discussionmentioning
confidence: 99%
“…The predominant clonal complexes in China are CC9 and CC8 in food and ST87 in clinics [53,54]. In the last decade, CC6 noticeably increased in significance as a causative agent of human listeriosis in Africa, Europe, and North America [31,33,[55][56][57]. In Russia, current human listeriosis is associated with the CC1, CC2, and CC20 strains [38].…”
Section: Discussionmentioning
confidence: 99%
“…The results observed in this study are similar to those reported for the largest outbreak of listeriosis to date (total of 1060 cases) that was attributed to a processed RTE meat in South Africa. That investigation also used the same cgMLST scheme (Moura et al ) and reported that clinical isolates were highly related to nonclinical isolates with <10 SNP and four allele differences suggesting a high probability of epidemiological relatedness (Smith et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Internationally recognized thresholds for cgMLST allele or SNP analysis differences between genetically related isolates are still being established. Publications describing the use of WGS within listeriosis outbreaks globally have reported ≤12 alleles by whole‐genome MLST or ranges of 0–50 SNPs as criteria to distinguish outbreak‐related isolates from unrelated isolates (Ruppitsch et al ; Jackson et al ; Moura et al ; Chen et al ; Moura et al ; Smith et al ). However, there is some variation between studies regarding the classification of strains as closely linked (Jackson et al ; Besser et al ).…”
Section: Resultsmentioning
confidence: 99%
“…The study materials consisted of 3 Campylobacter jejuni strains (one reference strain ATCC 33560 and two isolated from poultry meat), 3 Listeria monocytogenes strains (one reference strain ATCC 19111 and two isolated from poultry meat), and 3 Salmonella Enteritidis strains (one reference strain ATCC 13076 and two isolated from poultry meat).…”
Section: Methodsmentioning
confidence: 99%